2015
DOI: 10.3945/jn.115.220541
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Relation between Plasma 25-Hydroxyvitamin D and Insulin Resistance Is Largely Attributable to Central Adiposity in Overweight and Obese Adults

Abstract: Central adiposity drives the association between plasma 25(OH)D and insulin resistance in overweight and obese adults. The trial was registered at clinicaltrials.gov as NCT00812409.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 82 publications
(111 reference statements)
1
16
1
Order By: Relevance
“…Consistent with the findings of the current study, prior studies found an inverse association of serum 25(OH)D concentrations with insulin resistance [1], [5], [6] and pro-inflammatory markers such as IL-6 and CRP [14], [15]. Similarly, multiple prior studies have shown an inverse association of BMI with 25(OH)D, which is attributed to the fat-soluble nature of vitamin D and sequestration into adipose tissue [2], [16]. However, these previous studies included relatively low numbers of black individuals, precluding definitive examination of race differences.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the findings of the current study, prior studies found an inverse association of serum 25(OH)D concentrations with insulin resistance [1], [5], [6] and pro-inflammatory markers such as IL-6 and CRP [14], [15]. Similarly, multiple prior studies have shown an inverse association of BMI with 25(OH)D, which is attributed to the fat-soluble nature of vitamin D and sequestration into adipose tissue [2], [16]. However, these previous studies included relatively low numbers of black individuals, precluding definitive examination of race differences.…”
Section: Discussionsupporting
confidence: 89%
“…There is some inconsistency in the literature, however [20][21][22]. Jorde et al [20], reported serum TC and LDL-C increased, instead of decreased, across quartiles of serum 25(OH)D concentration (i.e., from the lowest to the highest quartiles), which contradicts the findings of our study, although they did find a decrease in TG and increase in HDL across the serum 25(OH)D quartiles.…”
Section: Serum 25(oh)d and Metabolic Health Riskscontrasting
confidence: 95%
“…Sixteen studies [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] were excluded as the data were not harmonious to calculate the effect size in the form of correlation. Five studies [ 87 , 88 , 89 , 90 , 91 ] were disqualified because of their study design, which was not well-suited with the study in progress.…”
Section: Resultsmentioning
confidence: 99%